Protective Factors against Self-Harm and Suicidality among Australian Indigenous Adolescents: A Strengths-Based Analysis of the Longitudinal Study of Indigenous Children - Islam, Md Irteja; Sharwood, Lisa; Chadwick, Verity; Esgin, Tuguy; Martiniuk, Alexandra (My University, 2022)
Background: Understanding and encouraging social and emotional well-being (SEWB) among Indigenous adolescents is vital in countering the impacts of colonisation and intergenerational trauma. As self-harm and suicidality are considered markers of poor SEWB among Indigenous communities, we aimed to identify the individual-level and community-level factors protecting Indigenous adolescents from self-harm and suicidality. Methods: Data came from Footprints in Time-The Longitudinal Study of Indigenous Children (waves 10 and 11), conducted among Indigenous families across Australia. A strengths-based analysis fitted multilevel logistic regression to explore associations with factors proposed as protective against self-reported self-harm and suicidality among Indigenous adolescents. Results: Our study cohort included 365 adolescents with complete data for the variables of interest. Adolescents had a mean (SD) age of 14.04 (0.45) years and a sex ratio of almost 1:1, and most were attending school (96.2%). Previous self-harm was reported by 8.2% (n = 30); previous suicidality was reported by 4.1% (n = 15). Individual-level factors protecting against self-harm and suicidality were being male, living in a cohesive family, and having low total Strengths and Difficulty Questionnaire scores (p < 0.05 for all). Residing in major cities compared with regional/remote areas was protective against self-harm (OR 5.94, 95% CI 1.31-26.81). Strong cultural identity was not found to be a protective factor against self-harm and/or suicidality in the sample. Conclusions: This study identified key individual- and community-level factors that can protect Australian Indigenous adolescents against self-harm and suicidality, particularly family cohesion. Identifying strengths for this at-risk population can inform prevention strategies, particularly for rural living adolescents with high distress.
International Journal of Environmental Research and Public Health
Keywords: Adolescents and youth; Health and wellbeing